2017
DOI: 10.1016/j.prevetmed.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Estimating population density for disease risk assessment: The importance of understanding the area of influence of traps using wild pigs as an example

Abstract: Population density is a key driver of disease dynamics in wildlife populations. Accurate disease risk assessment and determination of management impacts on wildlife populations requires an ability to estimate population density alongside management actions. A common management technique for controlling wildlife populations to monitor and mitigate disease transmission risk is trapping (e.g., box traps, corral traps, drop nets). Although abundance can be estimated from trapping actions using a variety of analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…Alternatively, spacing the bait sites at farther distances will allow for a larger geographic focus but a lower overall proportion of wild pigs will be removed. 80 Our results showed evidence that consumption of the biomarker bait varied by sex of wild pigs. Despite males and females having similarly sized home ranges, males visited ∼ 37% more bait sites and thus had more encounters with the bait.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Alternatively, spacing the bait sites at farther distances will allow for a larger geographic focus but a lower overall proportion of wild pigs will be removed. 80 Our results showed evidence that consumption of the biomarker bait varied by sex of wild pigs. Despite males and females having similarly sized home ranges, males visited ∼ 37% more bait sites and thus had more encounters with the bait.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, bait sites placed at a density of one site per ≤ 1.5 km 2 should theoretically expose all encompassed wild pigs to the bait. Alternatively, spacing the bait sites at farther distances will allow for a larger geographic focus but a lower overall proportion of wild pigs will be removed …”
Section: Discussionmentioning
confidence: 99%
“…Wild pigs in the drier ecoregions are predicted to move more because water resources are further away on average. Thus, ecoregion may describe numerous characteristics of a landscape, and could be a simple predictor of movement levels which is valuable for planning management programs across a large spatial scale [81, 82]. …”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that extrinsic factors such as weather could result in different movement reaction norms as a function of individual-level attributes. For example, perhaps adult males show a different reaction norm to temperature relative to females such as [81] found, where home range sizes of males were not affected by drought conditions but female home range sizes changed according to food availability and temperature constraints. Quantifying these individual-based differences in reaction norms could improve our fundamental understanding of movement capacity and lead to better prediction of how meteorological changes may impact population ecology.…”
Section: Discussionmentioning
confidence: 99%
“…If the bias were the other way and camera placement was less likely to detect wild pigs than we would be underestimating the occupancy of wild pigs which would be a considerable problem. Previous work on wild pigs has shown that baiting usually attracts pigs within a * 1.7 km radius (Davis et al 2017) and up to 10 km (N. Snow unpublished data). Therefore, it is likely that pigs within the 2 km 9 2 km sites would be detected if present.…”
Section: Discussionmentioning
confidence: 97%